Are Homemade "Pesticides" Legal? - Brett Bultemeier; Jason Ferrell (EDIS)
Interest around pesticides and possible alternatives to them have increased in recent years. As individuals seek out possible alternatives, some consider making their own solutions to pest control. Homemade pesticide recipes abound online and are commonly seen in various social media platforms. This new 3-page publication of the UF/IFAS Pesticide Information Office looks at the legality of these mixes, when and where they can be used, and what other considerations need to be taken into account when utilizing these mixes. Written by Brett Bultemeier and Jason Ferrell. https://edis.ifas.ufl.edu/pi288